The Gulf Conflict: Diplomacy and War In the New World Order by Lawrence Freedman and Efraim Karsh. Princeton, NJ: Princeton University Press, 1993. (American Journal of Islam and Society, 1997)
Writers have compared the media frenzy of the Gulf War to the coverage ofa football game. Critics noted the pep rally atmosphere created by journalists(Charles Osgood's description of US bombing as a "marvel"; Dan Rather's"Congratulations on a job wonderfully done."). A Chicago Tribune cartoon portrayedSaudi and Kuwaiti emirs in luxury boxes awaiting the war, heckling Bush to “Throw the bomb!” Perhaps it was that pause in the second week of thebombing, allowing most US soldiers to watch the Super Bowl, but Americansdid seem to confuse the war with a sporting event. Both features perceived goodguys and bad guys, satisfying but guilt-free violence, little sympathy for thecasualties . . . and plenty of cheerleaders.Books about the Gulf War extend this comparison to sports coverage. Afterthe big game, our fist wave of analysts report from postgame interviews. Theseare generally shallow and simplistic, breathless with elation and self-glory.Comparable books on the Gulf War, including biographies of Schwarzkopf,Powell, and Bush, now cram the discount tables at the large booksellers. Insports, the second wave of analysts, back in the studio, offer somewhat meatierexplanations and more subtle rationalizations for the events just reported. Theiremotions are thinly concealed in a semblance of objectivity ...